DAMPAK MANAJEMEN KUALITAS TOTAL DAN INTEGRASI RANTAI PASOK TERHADAP KINERJA PERUSAHAAN EKSPEDISI - Lumban Gaol, Juan Oscar Maulana; Wahyuningsih; Sigiro, Semton Vicktor (Business, Economics dan Entrepreneurship, 2024)
Companies need to pay attention to various aspects to achieve success amidst intense competition. Business developments encourage companies to adapt, with company performance and supply chain integration as key factors in success. Company, which operates in the domestic and international expedition sector, must ensure service quality to remain competitive. This research was conducted to determine the impact of supply chain integration on the performance of the Logistc company. This research is included in the type of "Hypothesis Testing" which aims to explain the relationship between factors in a particular situation and is exploratory in nature, where the researcher looks for new ideas and relationships between phenomena that have not yet been formulated. Data was collected through online surveys and direct interviews at Company, with a total employee population of 173 people, and a sample of 120 people taken using the quota sampling technique.The data collection method uses a questionnaire with 21 questions related to the influence of supply chain integration on company performance. Data analysis involved tests of validity, reliability and classical assumptions, including normality, multicollinearity, autocorrelation and heteroscedasticity tests, as well as the F test and t test to test the simultaneous and partial influence of each variable. The results of the analysis show that Supply Chain Integration has a significant negative effect on various aspects of company performance. In Hypothesis 1, it was found that Supply Chain Integration has a negative influence on Service Quality, with a coefficient value of β1 = -0.724 and a significance of 0.0000 < 0.05. Likewise in Hypotheses 2 and 3, Supply Chain Integration shows a significant negative influence on other performance indicators and overall company performance, with B coefficients of -0.721 and -0.768, respectively. These findings emphasize that companies must carefully manage supply chain integration, ensuring efficiency and good communication between partners and business units so as not to hamper performance. Evaluation of the integration strategy implemented is very important to achieve business goals and improve company performance.